1976
DOI: 10.3109/inf.1976.8.issue-3.13
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia Enterocolitica Infection in Patients with Acute Surgical Abdominal Disease: A Prospective Study

Abstract: The rate of yersiniosis in patients with acute abdominal disease was studied in a 16-month prospective investigation in 1972-1973 of 205 acutely ill patients referred to a surgical clinic of a Copenhagen City hospital with complaints of abdominal pain suggestive of appendicitis. Yersinia enterocolitica, biotype 4, was isolated from 11 patients (5.4%), 8 of whom were children. Yersinia was grown from faeces in 8 cases and from appendix of all 9 patients operated upon. Rising or falling agglutinin titres larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…It has been reported previously that pseudoappendicitis may occur leading to surgery (7,28). In the present study, appendicitis was not found, but the three surgical patients had mesenteric lymphadenitis.…”
Section: Discussionmentioning
confidence: 39%
“…It has been reported previously that pseudoappendicitis may occur leading to surgery (7,28). In the present study, appendicitis was not found, but the three surgical patients had mesenteric lymphadenitis.…”
Section: Discussionmentioning
confidence: 39%
“…4 However, chronic diarrhoea has also been described.5 In older children Y. enterocolitica infection has often been associated with mesenterial lymphadenitis causing an acute, appendicitis-like disease. 6 It has recently been shown that Y. enterocolitica from human sources is invasive for human epithelial cells in vitro.7-9 We have demonstrated polymorphonuclear leucocytes in the stools of patients with Y. enterocolitica infection, and suggested an association between the invasiveness of the pathogen, clinical exudative diarrhoea, and the presence of faecal leucocytes.9…”
mentioning
confidence: 99%
“…Yersinia enterocolitica causes a variety of illnesses in humans, such as gastroenteritis (6), pseudoappendicitis (8), nonsuppurative arthritis (26), septicemia (21), and suppurative infections (20). Gastroenteritis in young children has recently become the most common clinical manifestation (6,12), and several large outbreaks of Y. enterocolitica have been reported from Canada (3), and New York State (4).…”
mentioning
confidence: 99%